Skin infiltrating T-cell profile of drug reaction with eosinophilia and systemic symptoms (DRESS) reactions among HIV-infected patients - Chimbetete, Tafadzwa; Choshi, Phuti; Pedretti, Sarah; Porter, Mireille; Roberts, Riyaadh; Lehloenya, Rannakoe; Peter, Jonathan (Frontiers in Medicine, 2023)
Introduction Drug Reaction with Eosinophilia Systemic Symptoms (DRESS) is more common in persons living with HIV (PLHIV), and first-line anti-TB drugs (FLTDs) and cotrimoxazole are the commonest offending drugs. Limited data is available on the skin infiltrating T-cell profile among DRESS patients with systemic CD4 T-cell depletion associated with HIV. Materials and methods HIV cases with validated DRESS phenotypes (possible, probable, or definite) and confirmed reactions to either one or multiple FLTDs and/or cotrimoxazole were chosen (n = 14). These cases were matched against controls of HIV-negative patients who developed DRESS (n = 5). Immunohistochemistry assays were carried out with the following antibodies: CD3, CD4, CD8, CD45RO and FoxP3. Positive cells were normalized to the number of CD3+ cells present. Results Skin infiltrating T-cells were mainly found in the dermis. Dermal and epidermal CD4+ T-cells (and CD4+/CD8+ ratios) were lower in HIV-positive vs. negative DRESS; p < 0.001 and p = 0.004, respectively; without correlation to whole blood CD4 cell counts. In contrast, no difference in dermal CD4+FoxP3+ T-cells was found in HIV-positive vs. negative DRESS, median (IQR) CD4+FoxP3+ T-cells: [10 (0–30) cells/mm2 vs. 4 (3–8) cells/mm2, p = 0.325]. HIV-positive DRESS patients reacting to more than one drug had no difference in CD8+ T-cell infiltrates, but higher epidermal and dermal CD4+FoxP3+ T-cell infiltrates compared to single drug reactors. Conclusion DRESS, irrespective of HIV status, was associated with an increased skin infiltration of CD8+ T-cells, while CD4+ T-cells were lower in HIV-positive DRESS compared to HIV-negative DRESS skin. While inter-individual variation was high, the frequency of dermal CD4+FoxP3+ T-cells was higher in HIV-positive DRESS cases reacting to more than one drug. Further research is warranted to understand the clinical impact of these changes.